Perancangan Sistem Pengamanan Data Berdasarkan Standar ISO 27001 pada Lingkungan Laboratorium Teknik Informatika - Taufiq Timur Warisaji; Guruh Wijaya; Lintang Setyo Kurniawati (Puslitbang Sinergis Asa Professional, 2026)
This study addresses the problem of inadequate information security systems in Informatics Engineering laboratories, which leads to high risks of data leakage, unauthorized access, and low user awareness of information security. The aim of this research is to design and implement an information security system based on the ISO/IEC 27001 standard to enhance the protection of information assets and establish sustainable security governance. The research employs a descriptive qualitative method consisting of literature review, needs analysis, risk assessment using a Risk Assessment Matrix, system design and implementation of security controls, and system evaluation through penetration testing and user compliance surveys. The results show that the implementation of technical security controls, such as data encryption, firewalls, and access management, significantly reduces data leakage risks and improves user compliance and awareness of information security practices. The study concludes that ISO/IEC 27001 is effective in establishing a structured and sustainable information security management system within the Informatics Engineering laboratory environment